A case of acute brucellosis associated with HIV infection in Turkey - Fatma Yekta Urkmez; Sevil Alkan (HIV & AIDS Review. International Journal of HIV-Related Problems)
Human brucellosis is a common public health problem in Turkey. Human immunodeficiency virus (HIV)-positive patients are vulnerable to co-infections and super-infections due to targeting the immune system. Because opportunistic infections are considered primarily, it is very difficult to detect co-infections, especially Brucella spp., in this patient group. In addition, non-specific clinical findings of brucellosis make diagnosis difficult. In this report, an HIV-positive patient with acute brucellosis was described. A 28-year-old male patient receiving antiretroviral therapy was admitted to the hospital with complaints of high fever and myalgia for the last two weeks. Physical examination revealed enlargement of bilateral cervical lymph nodes and enlargement of bilateral inguinal lymph nodes. Primarily, opportunistic infections were investigated in this patient. Brucella spp. was detected in blood cultures taken due to high fever. Subsequently, the patient was diagnosed with brucellosis. We presented this case report with the purpose of drawing more attention to the clinical diagnosis of brucellosis. In addition, we recommend that clinicians should be more cautious about fever of unknown origin in HIV-positive patients, especially in regions where brucellosis is endemic. In the presence of newly developing fever and lymphadenopathy in HIV-infected individuals, opportunistic infections as well as other infectious diseases, including brucellosis, should be considered.